Deep brain stimulation for movement disorders. Issue 1 (3rd February 2010) - Thevathasan, Wesley; Gregory, Ralph
Abstract : Deep brain stimulation is now considered a routine treatment option for selected patients with advanced Parkinson's disease, primary segmental and generalised dystonia, and essential tremor. The neurosurgeon is responsi ble for the accurate and safe placement of the electrodes and the neurologist for the careful selection of patients and titration of medication against the effects of stimulation. A multidisciplinary team approach involving specialist nurses, neuropsychologists and neurophysiologists is required for a successful outcome. In this article we will summarise the key points in patient selection, provide an overview of the surgical technique, and discuss the beneficial and adverse outcomes that can occur.